New coxsackievirus B4 genotype circulating in Inner Mongolia Autonomous Region, China. - Xiaoling Tian; Yong Zhang; Suyi Gu; Yaochun Fan; Qiang Sun; Bo Zhang; Shaohong Yan; Wenbo Xu; Xueen Ma; Wenrui Wang (PLoS ONE)
Hand, foot, and mouth disease (HFMD) surveillance was initiated in the Inner Mongolia Autonomous Region of China in 2007, a crucial scrutiny for monitoring the prevalence of enterovirus serotypes associated with HFMD patients. However, this surveillance mostly focused on enterovirus 71 (EV-A71) and coxsackievirus A16; therefore, information on other enterovirus serotypes is limited. To identify the other circulating enterovirus serotypes in the HFMD outbreaks in Inner Mongolia in 2010, clinical samples from HFMD patients were investigated. Six coxsackievirus B4 (CVB4) strains were isolated and phylogenetic analyses of VP1 sequences were performed. Full-length genome sequences of two representative CVB4 isolates were acquired and similarity plot and bootscanning analyses were performed. The phylogenetic dendrogram indicated that all CVB4 strains could be divided into 5 genotypes (Genotypes I-V) with high bootstrap support (90-100%). The CVB4 prototype strain (JVB) was the sole member of genotype I. CVB4 strains belonging to genotype II, which were once common in Europe and the Americas, seemingly disappeared and gave way to genotype III and IV strains, which appear to be the dominant circulating strains in the world. All Chinese CVB4 strains belonged to Genotype V, a newly identified genotype supported by a high bootstrap value (100%), and are circulating only in mainland of China. Intertypic recombination occurred in the Chinese CVB4 strains with novel unknown serotype EV-B donor sequences. Two Chinese CVB4 strains had a virulent residue at position 129 of VP1, and one strain also had a virulent residue at position 16 of VP4. Increased surveillance is needed to monitor the emergence of new genetic lineages of enteroviruses in areas that are often associated with large-scale outbreaks. In addition, continued monitoring of enteroviruses by clinical surveillance and genetic characterization should be enhanced.